2000
DOI: 10.1016/s0006-3495(00)76522-2
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Molecular Dynamics and Diffusion Model of Single Proton Conduction through Gramicidin

Abstract: We develop a model for proton conduction through gramicidin based on the molecular dynamics simulations of Pomès and Roux (Biophys. J. 72:A246, 1997). The transport of a single proton through the gramicidin pore is described by a potential of mean force and diffusion coefficient obtained from the molecular dynamics. In addition, the model incorporates the dynamics of a defect in the hydrogen bonding structure of pore waters without an excess proton. Proton entrance and exit were not simulated by the molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
86
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(89 citation statements)
references
References 40 publications
3
86
0
Order By: Relevance
“…In the 10<s<30 range it has a relatively linear shape and bends up at s>30 ps −1 . We found that at very small s the smooth shape of D̂ (s) function is corrupted by a singularity near s=0, as has been observed previously [42]. We observed that the location of the singularity depends on the amount of MD sampling: longer simulations shifted the singularity to smaller s. For a 30 ns MD simulation the onset of the singularity went down to s=0.05 ps −1 .…”
Section: Calculation Of Diffusion Constant Of K + In Bulk Watersupporting
confidence: 83%
“…In the 10<s<30 range it has a relatively linear shape and bends up at s>30 ps −1 . We found that at very small s the smooth shape of D̂ (s) function is corrupted by a singularity near s=0, as has been observed previously [42]. We observed that the location of the singularity depends on the amount of MD sampling: longer simulations shifted the singularity to smaller s. For a 30 ns MD simulation the onset of the singularity went down to s=0.05 ps −1 .…”
Section: Calculation Of Diffusion Constant Of K + In Bulk Watersupporting
confidence: 83%
“…(120) satisfies the condition of detailed balance under equilibrium conditions in the absence of net flux, and the stochastic evolution of the system obeys the multi-dimensional Smoluchowski diffusion Eq. (10) as dz becomes increasingly small (McGill & Schumaker, 1996;Schumaker et al 2000Schumaker et al , 2001. The resulting equations are closely related to the coupled multi-ion diffusion theory that was formulated by Stephan et al (1983).…”
Section: Discrete-state Markov Chainsmentioning
confidence: 71%
“…We will review the single-ion NP model (Lewitt, 1986 ;McGill & Schumaker, 1996), which is of particular interest because it can be solved analytically. We will also describe framework models based on continuous time discrete-state Markov chains, which can handle multi-ion pores (McGill & Schumaker, 1996;Schumaker et al 2000Schumaker et al , 2001Bernèche & Roux, 2003). Such framework models are the most convenient and powerful approaches to incorporate the information extracted from MD simulations, such as the PMF and the diffusion coefficient.…”
Section: From MD To I-v : a Practical Guidementioning
confidence: 99%
“…The stochastic Brownian motion of the multiion system was implemented as a continuous-time Markov chain with discrete states corresponding to the ion positions, and the state-to-state random walk was constructed by generating exponentially distributed random survival times. Such a Markov random walk satisfies the condition of detailed balance under equilibrium conditions in the absence of net flux, and the stochastic evolution of the system obeys a multidimensional Smulochowsky (Nernst-Planck) diffusion equation as ␦Z becomes increasingly small (30)(31)(32). The forward and backward transition rates are given by (e.g., for ion 1)…”
Section: Theory and Methodsmentioning
confidence: 99%